What’s new in the treatment of childhood psoriasis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
Taking the cue from a report regarding the use of biologics in childhood psoriasis, the Author reviews the treatment of psoriasis in children. At this age of life it is useful to consider, in addition to general criteria such as disease duration and transient effectiveness of any therapy, specific age-related criteria, as the different esthetic significance in children and adolescents, the weight / skin surface ratio, the greater likelihood of adverse long term side effects, as the risk for cancer, the less intense symptoms and finally the greater dependence of the child from the family in weighing psoriasis.